Jurnal Penyuluhan: Peran Ketua Kelompok Wanita Tani dalam Pemanfaatan Lahan Pekarangan yang Berkelanjutan - Rindi Metalisa, Amiruddin Saleh, Prabowo Tjitropranoto (PPs ILMU PENYULUHAN PEMBANGUNAN IPB, 2014)
The growing food needs become a significant issue due the population increases, farming lands converted, and climate change. One of attempt to support food needs is utilizing gardening that are environmental friendly and based on local resources. Optimizing gardening through women farmers group can be a huge potential in sustainability gardening.